Ambipolar organic field-effect transistors based on solution-processed single crystal microwires of a quinoidal oligothiophene derivative. Issue 27 (17th February 2015) - Ribierre, J. C.; Zhao, L.; Furukawa, S.; Kikitsu, T.; Inoue, D.; Muranaka, A.; Takaishi, K.; Muto, T.; Matsumoto, S.; Hashizume, D.; Uchiyama, M.; André, P.; et al.
Abstract : Single crystal microwires of a quinoidal oligothiophene derivative were prepared by a solution-processing method and used in high mobility ambipolar organic transistors. Abstract : A simple and versatile solution-processing method based on molecular self-assembly is used to fabricate organic single crystal microwires of a low bandgap quinoidal oligothiophene derivative. Individual single crystal microwire transistors present well-balanced ambipolar behaviour with hole and electron mobilities as high as 0.4 and 0.5 cm 2 V −1 s −1, respectively.